How to Improve Teacher Organizational Commitment? The Impact of Transformational Leadership, Achievement Motivation, and Organizational Culture - Ni Kadek Lolik Anawati; I Gede Aryana Mahayasa (Management and Applied Social Studies Review, 2023)
Purpose – The aim of this study was to examine how transformational leadership, achievement motivation, and organizational culture affect teacher's commitment to the organization. Methodology – This research adopted a quantitative causality approach to investigate the teaching population of civil servant and honorary teachers at SMP 2 Ubud. The study involved 88 respondents, and the sampling technique used was the saturated sampling method (census method). The data for the study was collected through questionnaires and interviews. Findings – The study's findings indicate that transformational leadership had a significant and positive impact on organizational commitment. Similarly, achievement motivation was found to have a positive and significant effect on organizational commitment. The study also revealed that organizational culture positively impacted organizational leadership, as well as transformational leadership, achievement motivation, and organizational culture all had a positive impact on organizational commitment. Originality – This research implies that the leaders should focus on inspiring their subordinates to consistently adhere to behavioral standards, provide tasks based on the experience of teachers, and increase the intensity of procurement activities that attract consumers' attention.